Comparing debian linux and windows server in project-based learning for network service configuration: effects on problem-solving skills in vocational education - Eliya Rahmawati Eliya; Mohammad Wildan Habibi Wildan (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2026)
The swift evolution of technological innovation has increased the demand for vocational graduates who possess strong technical competence and problem-solving skills in network system administration. Debian Linux and Windows Server are two operating systems widely used for configuring and managing network services in both educational and industrial environments. However, few studies have investigated the effect of server systems, specifically Linux and Windows, on the enhancement of students' problem-solving ability. In an attempt to fill this gap, this study examined the problem-solving skills of vocational students to the degree that Project-Based Learning (PjBL) involved server systems. With regard to the role of the server platform, this study empirically posits the characteristics that are ideal for the enhancement of problem-solving skills. The study was experimental and utilized both a control and experimental group of vocational students. The study was developed based on previously published research and the study author’s experience and involved an instrument for the assessment of the degree of students' problem-solving skills. The data were analyzed quantitively. The outcomes demonstrated that problem-solving skills for both Debian Linux and Windows Server systems were improved; Windows Server improved skills even further when used with PjBL in a structured, planned manner. PjBL alone improved the skills of students. Additionally, the study provided valuable evidence for the role of pedagogy in technical education. The findings of this research demonstrates theoretical significance for the interaction of the discipline of vocational education. They are also practical for educators, as they provide guidance in the processes of selection and fusion of server systems and educational methodologies that promote critical and advanced cognitive skills in students.